1\\x=5" alt="\sqrt{3x+1}=x-1,x-1\geq0,x\geq1\\(\sqrt{3x+1})^2=(x-1)^2\\3x+1=x^2-2x+1\\x^2-5x=0\\x(x-5)=0\\x_{1}=0,x_{2}=5\\0<1,5>1\\x=5" align="absmiddle" class="latex-formula">
![f(x)=x^3-3x^2+4\\f`(x)=3x^2-6x\\f`(x)=0\\3x^2-6x=0\\3x(x-2)=0 f(x)=x^3-3x^2+4\\f`(x)=3x^2-6x\\f`(x)=0\\3x^2-6x=0\\3x(x-2)=0](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3-3x%5E2%2B4%5C%5Cf%60%28x%29%3D3x%5E2-6x%5C%5Cf%60%28x%29%3D0%5C%5C3x%5E2-6x%3D0%5C%5C3x%28x-2%29%3D0)
+ - +
________________ 0 ________________ 2 _____________
f(x) возрастает на ![(-\infty;0)\cup(2;+\infty) (-\infty;0)\cup(2;+\infty)](https://tex.z-dn.net/?f=%28-%5Cinfty%3B0%29%5Ccup%282%3B%2B%5Cinfty%29)
f(x) убывает на ![(0;2) (0;2)](https://tex.z-dn.net/?f=%280%3B2%29)
![x^2=4\\ x=+-2 x^2=4\\ x=+-2](https://tex.z-dn.net/?f=x%5E2%3D4%5C%5C+x%3D%2B-2)
![S=\int\limits^2_{-2} {x^2} \, dx =\frac{x^3}{3}|^2_{-2} }=\frac{8}{3}-\frac{-8}{3}=\frac{16}{3}=5\frac{1}{3} S=\int\limits^2_{-2} {x^2} \, dx =\frac{x^3}{3}|^2_{-2} }=\frac{8}{3}-\frac{-8}{3}=\frac{16}{3}=5\frac{1}{3}](https://tex.z-dn.net/?f=S%3D%5Cint%5Climits%5E2_%7B-2%7D+%7Bx%5E2%7D+%5C%2C+dx+%3D%5Cfrac%7Bx%5E3%7D%7B3%7D%7C%5E2_%7B-2%7D+%7D%3D%5Cfrac%7B8%7D%7B3%7D-%5Cfrac%7B-8%7D%7B3%7D%3D%5Cfrac%7B16%7D%7B3%7D%3D5%5Cfrac%7B1%7D%7B3%7D)
0\\x(x-3)>0\\x\in(-\infty;0)\cup(3;+\infty)\\\\x^2-3x=(\frac{1}{2})^{-2}\\x^2-3x=4\\x^2-3x-4=0\\x_{1}=-1,x_{2}=4,x\in(-\infty;0)\cup(3;+\infty)\\x=4" alt="log_{\frac{1}{2}}(x^2-3x)=-2\\\\x^2-3x>0\\x(x-3)>0\\x\in(-\infty;0)\cup(3;+\infty)\\\\x^2-3x=(\frac{1}{2})^{-2}\\x^2-3x=4\\x^2-3x-4=0\\x_{1}=-1,x_{2}=4,x\in(-\infty;0)\cup(3;+\infty)\\x=4" align="absmiddle" class="latex-formula">